2023
DOI: 10.3390/ijms242216353
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Targeted Iron Therapy in Alzheimer’s Disease

Jian Wang,
Jiaying Fu,
Yuanxin Zhao
et al.

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease worldwide. β-amyloid plaque (Aβ) deposition and hyperphosphorylated tau, as well as dysregulated energy metabolism in the brain, are key factors in the progression of AD. Many studies have observed abnormal iron accumulation in different regions of the AD brain, which is closely correlated with the clinical symptoms of AD; therefore, understanding the role of brain iron accumulation in the major pathological aspects of AD is critical for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 165 publications
0
0
0
Order By: Relevance
“…Finally, translating the growing understanding of iron-induced neuroinflammation into effective therapeutic and preventative strategies could be fruitful. This could involve exploring chelation therapy to remove excess iron from the brain [ 62 ], developing anti-inflammatory drugs targeted specifically for the brain, and investigating dietary and lifestyle modifications that can mitigate iron accumulation and neuroinflammation. While further research is clearly needed, the current evidence suggests a strong plausible connection among alcohol-related iron overload, neuroinflammation, and cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, translating the growing understanding of iron-induced neuroinflammation into effective therapeutic and preventative strategies could be fruitful. This could involve exploring chelation therapy to remove excess iron from the brain [ 62 ], developing anti-inflammatory drugs targeted specifically for the brain, and investigating dietary and lifestyle modifications that can mitigate iron accumulation and neuroinflammation. While further research is clearly needed, the current evidence suggests a strong plausible connection among alcohol-related iron overload, neuroinflammation, and cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review involving two iron chelating agents, M30 and HLA20, suggested the neuroprotective role of iron-chelating agents in animal models by reducing neurodegenerative pathology, upregulating signalling pathways that provide neuronal protection, and providing positive behavioural modification [ 37 ]. Several studies have recently proposed the utilisation of iron-chelating agents for the treatment of Alzheimer’s disease [ 62 , 64 ]. Another study used alpha-lipoic acid in transgenic mice models, which prevented tau-hyperphosphorylation and reduced oxidative stress, inflammation, and ferroptosis in neuronal cells [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, clioquinol has been withdrawn from the antibiotic market due to its association with subacute myelo-optic neuropathy. Hence, clinical investigations of recently developed second-generation clioquinol are important [6,[130][131][132].…”
Section: Alzheimer's Disease Therapies That Might Target Elementsmentioning
confidence: 99%
“…DFO, DFP, and DFX are Food and Drug Administration (FDA)-approved iron chelators capable of crossing the BBB [ 42 ]. Recently, it has been shown that these agents can lower iron accumulation in patients with AD [ 43 ]. DFO binds iron in a 1:1 ratio and is a hexadentate ligand [ 44 ].…”
Section: Metal Chelators For the Potential Treatment Of Admentioning
confidence: 99%